Rapidly progressive interstitial lung disease associated with dermatomyositis—Longitudinal course of anti‐MDA5 antibody titer in two cases. Issue 4 (29th March 2021) - Awaji, Kentaro; Asano, Yoshihide; Fukui, Yuki; Oka, Tomonori; Toyama, Tetsuo; Sato, Shinichi
Abstract: Antimelanoma differentiation‐associated gene 5 antibody (anti‐MDA5 Ab)‐positive dermatomyositis frequently develops life‐threatening rapidly progressive interstitial lung disease (RP‐ILD). The longitudinal dynamics of antibody titers reflects treatment responses, and negative conversion of anti‐MDA5 Ab leads to the prevention of RP‐ILD relapse. Case 1 finally achieved negative conversion of anti‐MDA5 Ab after 18‐month immunosuppressive therapy despite early diagnosis from skin manifestations. Case 2 showed re‐elevation of anti‐MDA5 Ab after tacrolimus discontinuation; immediate restart of tacrolimus recovered it without relapse. These cases suggest that anti‐MDA5 Ab monitoring is essential to determine therapeutic strategy in dermatomyositis patients with RP‐ILD during both initial and maintenance phases. Abstract : We report the longitudinal dynamics of anti‐MDA5 Ab titers of two cases. Case 1 finally achieved negative conversion of anti‐MDA5 Ab after 18‐month immunosuppressive therapy despite early diagnosis, and Case 2 showed re‐elevation of anti‐MDA5 Ab after tacrolimus discontinuation even though long‐term negative conversion was maintained. Anti‐MDA5 Ab monitoring is quite useful to determine therapeutic strategy during both initial and maintenance phases.